Open-label study of treatment with alendronate sodium plus vitamin D in men and women with osteoporosis in Thailand - Thawee Songpatanasilp; Sattaya Rojanasthien; Pansak Sugkraroek; Boonsong Ongphiphadhanakul; Lamar Robert; Chongchit Sripun Robert; Sirichai Luevitoonvechkij; Arthur C. Santora (BMC Musculoskeletal Disorders, 2018)
Abstract Background It is generally believed that Thai people do not suffer from hypovitaminosis D because there is abundant sunlight throughout the year, and that taking vitamin D supplements could result in abnormally high levels of vitamin D. This is a Thai FDA-driven study to investigate this risk over a period of 26 weeks of taking alendronate sodium/vitamin D3 combination tablets. Methods Osteoporosis patients in Thailand were recruited to a multicenter, open-label, 6-month trial of oral alendronate sodium 70 mg/vitamin D3 5600 IU. Patients received study medication once a week for 26 weeks. Serum 25-hydroxyvitamin D (25(OH)D) and Beta-CrossLaps (β-CTx) levels were measured at baseline and 26 weeks. The primary endpoint was the proportion of patients with 25(OH)D ≥ 50 ng/mL at week 26; it was hypothesized that 26 weeks’ treatment would not result in 25(OH)D serum levels ≥ 50 ng/mL in > 7% of osteoporosis patients. Results One hundred ninety-eight patients were recruited. At baseline, 67.2% of the patients had 25(OH)D < 30 ng/mL; this declined to 34.4% by week 26. The mean 25(OH)D level improved from 27.8 ng/mL at baseline to 33.6 ng/mL at week 26. Five patients (2.69% of the full analysis set) had 25(OH)D levels ≥ 50 ng/mL at 26 weeks. The highest 25(OH)D level, 64.3 ng/mL, was observed in a patient whose baseline level was 102.2 ng/mL. The majority (62.9%) of the patients had optimal 25(OH)D levels (30–50 ng/mL). β-CTx levels were reduced by 57.7% after 26 weeks’ treatment. No clinically significant cases of hypercalcemia which could be associated with hypervitaminosis D were identified during physical examination, in vital signs, or in laboratory results. Overall, 73 patients (36.9%) reported at least one adverse event (AE), with 13 (6.6%) reporting drug-related AEs. Four patients discontinued due to AEs, two of which were drug-related. Serious AEs were reported for four patients, of which one was considered drug-related. Conclusions Oral alendronate sodium 70 mg plus vitamin D3 5600 IU once weekly had an acceptable safety profile in this study, and increased serum 25(OH)D and reduced β-CTx levels in osteoporosis patients. This treatment improved 25(OH)D levels, without causing abnormally high levels, after 26 weeks’ treatment. Trial registration Clinical Trials.gov NCT01437111, Registered September 19, 2011.